Utility of MitraClip XTR System in Percutaneous Edge-To-Edge Mitral Valve Repair for Severe Flail Leaflet - Al-Hijji, Mohammed (Heart Views, 2020)
Transcatheter mitral valve (MV) edge-to-edge repair provided alternative solutions to high surgical risk patients with degenerative MV regurgitation (MR) and patients with functional MR leading to symptomatic heart failure. However, the procedure cannot be performed in certain MV anatomy such as excessive mitral annular or leaflet calcification with coexisting stenosis or excessive flail leaflet with wide gap and width. The introduction of MitraClip XTR system with its extended arms provided a wider range of MV anatomies that can be treated with MV edge-to-edge repair. In this report, we present the successful treatment of excessive flail posterior leaflet with MitraClip XTR device.